Career Goal Setting Knowledge and Practices among Mid-West University Students - Shahi, Sushil Kumar (Journal of Entrepreneurship & Management Studies, 2024)
This study examines Mid-West University student's career goal setting knowledge and practices among Mid-West University students. Main objective of the research is to assess and describe MU student's knowledge and real life practices in the course of their career goal setting efforts and getting desired success. Thematic analysis associated with qualitative approach was used to analyze qualitative data derived from students studying at Mid-West University School of Management (MUSOM), Central Campus of Education and Central Campus of Humanities and Social Sciences. To explore and describe the ways students perceive career goal setting process, experience faculty member's teaching, view linkage between courses and career, importance of hearing parents, conducting internship, ideological influence, pressure, and network in terms of shaping career path. 220 graduates were asked questions related to career goal setting and practices via email and group interview. Six themes were generated from the data collected through the purposive sampling. 20 students were provided the list of questions for collection of more comprehensive information and 200 students were provided just list of activities they could use when developing career goal. The interpreted data offers the conclusion that graduates lacked analytical skill to contextualize their understanding. But they clearly understood different activities such as seminar, presentation, workshop, research, networking, planning and developing communication and leadership skills, and continued reading for making them aware of developing relevant career goal and achieving practical outcomes.